Integrating strategic management accounting with risk management in the digital transformation period to improving business performance at import-export companies - NGUYEN, Thi Thuy Viet; NGUYEN, Thi Thanh Dan (International Journal of Innovative Research and Scientific Studies, 2025)
The study evaluates the ability to integrate Strategic Management Accounting (SMAu) and Enterprise Risk Management (ERM), which affects the business performance (PER) of import-export companies in Vietnam during the digital transformation period (DT). The author conducted a survey and collected 262 observation samples with 9 factors affecting the PER of Vietnamese import-export companies (IOCs). The study’s objective is to identify the factors that positively affect SMAu and ERM, thereby integrating SMAu and ERM with the support of DT to enhance the PER of IOCs. The factors affecting SMAu and ERM include CEO capacity, enterprise size (SIZE), competitiveness (COM), and risk protection policy (RMP). The two intermediate factors, SMAu and ERM, positively affect the PER of IOCs. The moderating factor affecting the research model is digital transformation, which has a positive impact on SMAu, ERM, and PER. As a result, the author has successfully built a research model integrating SMAu with ERM in the context of digital transformation tools (DT) so that the company can improve its PER.